Universities as Agencies
XIV, 278 p. 9 illus.
Keywords: This book discusses how modern universities increasingly use reputation management in relation to internal and external challenges. Universities are increasingly characterized by social embeddedness, relating to many external stakeholders and international markets of students, researchers and research projects. This implies global pressure to standardize, formalize and rationalize their internal organization. The book uses data from China, Norway and US to show how reputation symbols are used and balanced, based on their web pages. Further, it uses extensive data from US universities to show how their internal organization structure is developing over time, related to three types of units/positions - development, diversity and legal offices and roles. Tom Christensen is Professor of Public Policy and Administration at Department of Political Science, University of Oslo. Åse Gornitzka is Professor of Public Policy and Administration at Department of Political Science, University of Oslo. Francisco O. Ramirez is Professor of Education and (by courtesy) Sociology, Stanford University.